Growth Patterns and Food Habits of Swamp Eel (Monopterus albus) from the Common Water of the Riau Main Stadium - Radhiyah Radhiyah; Windarti Windarti; Ridwan Manda Putra (Universitas Riau, 2021)
Swamp eel is one of the freshwater fish that live in the waters around the Riau Main Stadium. This research aims to understand the growth pattern, feeding habit and to determine the type of food present in the fish’s stomach. This research was carried out in September-October 2020. Sampling was conducted five times, once/week, using a fish rod and bamboo fish trap. There were 52 fishes captured (TL 291-613 mm and weight 30-132 gr). The stomach content was analyzed using a volumetric method and the Preponderance Index (PI) of each type of food was calculated. The length-weight relationship shown that the growth of female, intersex and male was negative allometric (b=2.40 in female, b=1,56 in intersex and b= 2,02 in male). Results showed that the food of M. albus in the waters around the Riau Main Stadium consists of insects (PI 49%), fish remains (PI 32%), mollusc (PI 9%), plants (PI 9%) and unidentified materials (1%). Based on data obtained, this fish categorized.